Modelling and analysis of electromagnetic force, vibration, and noise in permanent magnet synchronous motor for electric vehicles under different working conditions considering current harmonics - Lixin Wang; Xiaoyuan Wang; Na Li; Tianyuan Li (IET Electric Power Applications, 2023)
Abstract The vibration and noise of the permanent magnet synchronous motor (PMSM) is mainly caused by its electromagnetic force. Harmonic currents affect the vibration, and noise performance of PMSM by influencing its electromagnetic force. The regularity of electromagnetic force, vibration, and noise characteristics of PMSM for electric vehicles (EVs) under different working conditions influenced by the harmonic currents is studied. Firstly, the analytical model of electromagnetic force under the action of a harmonic current is derived, and the influence of harmonic currents on the electromagnetic force of PMSM is summarised. Secondly, a multi‐physical field coupled vibration, and noise calculation model considering harmonic currents is established using the finite element method, and the vibration, and noise characteristics of PMSM under different operating conditions are analysed. The results show that the harmonic currents have different patterns of influence on the vibration, and noise of the PMSM due to the different advance angles and the saturation degree of the magnetic material under different working conditions. Finally, the validity of the theoretical analysis is verified by experiments, which has academic significance for vibration, and noise reduction of PMSMs for EVs.